Water‐Abundant Electrolytes: Towards Safer and Greener Aqueous Zinc‐Metal Batteries - Long Qian; Rui Yao; Prof. Cheng Yang (ChemElectroChem, 2023)
Abstract Aqueous Zn metal batteries have been regarded as promising candidates as an alternative to Li‐ion batteries in large‐scale energy storage systems due to their low‐cost, safe and environmentally benign advantages. However, because of the introduction of solvent water, several problems, for example dendrites, parasite reactions, hydrogen evolution, and so on, are brought into aqueous Zn metal batteries. Regrettably, when trying to solve these problems, most efforts have taken the form of adding a large amount of non‐aqueous components, which are usually harmful to the environment and not conducive to greener and safer aqueous batteries. In this Concept, we will introduce several electrolyte systems and mainly focus on how to build a water‐abundant electrolyte with fewer non‐aqueous components. This work will review the literature and offer instructive guidance for environmentally benign Zn metal batteries.